A-167 The Role of Epilepsy Knowledge and Treatment Beliefs in Medication Self-Management Among Diverse People with Epilepsy. (17th August 2022) - Crook, Cara; Margolis, Seth A; Davis, Jennifer; Gonzalez, Jeffrey S; Grant, Arthur C; Nakhutina, Luba
Abstract: Objective: Research into medication adherence remains limited among ethnically diverse people with epilepsy (PWE). We characterized self-reported reasons for suboptimal adherence in this population. Next, we sought to replicate a previously established link between negative medication beliefs and worse adherence. Finally, we explored whether epilepsy knowledge moderates the beliefs-adherence relationship. Method: Sixty-three PWE (Age=42.1±13.2; Education=12.6±2.4 years; 60% female; 79% Black; 19% Hispanic/Latinx; 5% Mixed Race) completed the Beliefs about Medicines Questionnaire (BMQ), Epilepsy Knowledge Profile (EKP), and Epilepsy Self-Management Scale's (ESMS) Medication Management subscale with nonadherent practices endorsed "sometimes, most of the time, or always" considered "suboptimal." Results: The four most prevalent suboptimal adherence practices were endorsed by 20-34% of participants and included not taking anti-seizure medications the same time every day, forgetting doses, not requesting refills before running out, and spreading out doses when running out. A considerable number of participants agreed/strongly agreed that medications were overused by prescribers (45.2%), that their medications concerned them (24.2%) or were harmful (19.4%). Epilepsy knowledge was fair (EKP=70.4%±9.5% correct). Harm and overuse beliefs were negatively correlated with adherence (r's=-0.27 and -0.32 with p's=.035 and .013, respectively). Epilepsy knowledge was unrelated to beliefs or adherence and did not moderate their relationship. Harm/overuse beliefs were combined (α=0.78) and their significant relationship with adherence (r=-0.34, p=.008) was unchanged after controlling for epilepsy knowledge (pr=-0.31, p=.017). Conclusions: In these diverse PWE, the most prevalent reasons for suboptimal medication adherence are behaviorally-mediated and may be modifiable. However, interventions addressing negative medication beliefs may be necessary to effect change over knowledge-based psychoeducation alone.